Applied Enantioselective Aminocatalysis: α‐Heteroatom Functionalization Reactions on the Carbapenem (β‐Lactam Antibiotic) Core. Issue 3 (11th December 2014) - Cele, Zamani E. D.; Arvidsson, Per I.; Kruger, Hendrik G.; Govender, Thavendran; Naicker, Tricia
Abstract: The carbapenem (β‐lactam antibiotic) scaffold serves as a useful nucleophile in organocatalytic diarylprolinol trimethylsilyl ether mediated α‐heterofunctionalization reactions leading to the formation of diverse products that bear multiple stereocenters in high diastereoselectivity and moderate to good yields. Abstract : A carbapenem intermediate serves as a useful nucleophile in organocatalyst‐mediated α‐heterofunctionalization reactions leading to the formation of diverse products.